Effect of visual stimuli on the subjective impression of pass-by sound transmitted into low-rise residential building. (1st December 2020) - Asakura, T.; Hashimoto, R.
Abstract: The effect of additionally presented visual stimuli on the subjective impression of the vehicle pass-by sound transmitted into a low-rise residential building was investigated based on the environmental simulation method combining the binaural sound auralization technieque and the three-dimensional spatial visualization technique. The exterior scenery seen from inside a residential room largely depends on the spatial relationship with the neighborring buildings and driveways around the evaluated site. In addition, the exterior scenery generally includes the pass-by vehicles running on the neighborring driveways, which are often the main source of the sound environment around the site. In this study, the variation of subjective impression of a vehicle pass-by sound caused by presenting various kinds of visual stimuli seen from the window of a residential room was discussed. As a basic study, the vehicle pass-by sound transmitted into the room via the façade was simulated by using the geometrical acoustic simulation. To increase the presence of the reproduced sounds, the auralized sounds were reproduced by dynamically changing the binaural room impulse response (BRIR) depending on the head rotation of the subjects. In contrast, the visual condition inside the evaluated rooms was simulated by using three-dimensional modeling software. Then, the effect of the auditory and visual stimuli on the impression of the environments inside a residential room was investigated by performing the subjective evaluation experiment based on the audiovisual simulation scheme. The obtained results indicated that the sound impression of the pass-by noise transmitted into the room was influenced by the additionally presented visual stimuli, but the extent of the influence on the impression differs depending on the detailed information included in the auditory and visual stimuli.